Red-emitting IrIII(C^N)2(P-donor ligand)Cl-type complexes showing aggregation-induced phosphorescent emission (AIPE) behavior for both red and white OLEDs. (September 2022) - Li, Huiying; Jia, Dongming; Yao, Chaofan; Jing, Yulin; Li, Bochen; Yang, Xiaolong; Sun, Yuanhui; Su, Bochao; Zhou, Guijiang; Jiao, Bo
Abstract: Two red-emitting Ir III (C^N)2 (P-donor ligand)Cl-type complexes bearing C^N ligands with carbazole functional group have been successfully prepared with different P-donor ligands of triphenylphosphine and triethylphosphine, respectively. The investigation of their phosphorescent behavior in the mixture of THF and water to reveal their aggregation induced phosphorescent emission (AIPE) ability, which is also indicated by their much higher phosphorescent quantum yield ( Φ P ) in doped film than those in the dilute solution. Mainly, their AIPE are induced by the blocked stretching motion of aromatic segments in C^N ligand and restrained the deformation of their coordinating skeletons. The AIPE complexes can possess AIE factor ( α AIE ) of ca. 7.4. In addition, the carbazole group can effectively promote hole transporting ability of the concerned AIPE emitters, which can benefit their electroluminescent ability. Hence, the Ir III (C^N)2 (P-donor ligand)Cl-type complexes can show decent EL efficiencies in the solution-processed red-emitting organic Light-emitting diodes (OLEDs) with a maximum external quantum efficiency ( η ext ) of 8.5%, a maximum current efficiency ( η L ) of 22.0 cd A −1 and a maximum power efficiency ( η P ) of 15.9 lm W −1 . Furthermore, as long-wavelength emitter, solution-processed white OLEDs (WOLEDs) have been constructed based on the red-emitting AIPE Ir III (C^N)2 (P-donor ligand)Cl-type complexes, which can play critical role in achieving stable white electroluminescent spectra at high luminescence. The concerned WOLEDs can show attractive EL efficiencies of 6.6%, 23.7 cd A −1 and 16.0 lm W −1 . All these results can provide valuable information for developing new AIPE materials with high EL ability. Graphical abstract: Image 1 Highlights: AIPE-active Ir III (C^N)(P-donor ligand)Cl-type complexes were prepared with different phosphine ligands. Solution-processed red-emitting OLED showed a peak CE of 22.0 cd A −1 . Solution-processed white OLED showed a peak CE of 24.8 cd A −1 with CIE (0.31, 0.38).